2015
DOI: 10.1111/desc.12370
|View full text |Cite
|
Sign up to set email alerts
|

Motor training at 3 months affects object exploration 12 months later

Abstract: The development of new motor skills alters how infants interact with objects and people. Consequently, it has been suggested that motor skills may initiate a cascade of events influencing subsequent development. However, only correlational evidence for this assumption has been obtained thus far. The current study addressed this question experimentally by systematically varying reaching experiences in 40 three-month-old infants who were not reaching on their own yet and examining their object engagement in a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 53 publications
5
93
0
1
Order By: Relevance
“…The current findings together with previous studies using active sticky mittens training indicate that this training paradigm influences cognitive, motor, and social development (Libertus, Joh, & Needham, 2016; Libertus & Needham, 2010, 2011; Sommerville, Woodward, & Needham, 2005; Gerson & Woodward, 2013; Skerry, Carey, and Spelke, 2013; Rakison & Krogh, 2012; Wiesen, Watkins, & Needham, 2016). Based on what we know about the nature of development, it is likely that experiences that stem from infants' own actions with their bodies (like sticky mittens training) would have beneficial effects on learning and development (e.g., Needham & Libertus, 2011).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The current findings together with previous studies using active sticky mittens training indicate that this training paradigm influences cognitive, motor, and social development (Libertus, Joh, & Needham, 2016; Libertus & Needham, 2010, 2011; Sommerville, Woodward, & Needham, 2005; Gerson & Woodward, 2013; Skerry, Carey, and Spelke, 2013; Rakison & Krogh, 2012; Wiesen, Watkins, & Needham, 2016). Based on what we know about the nature of development, it is likely that experiences that stem from infants' own actions with their bodies (like sticky mittens training) would have beneficial effects on learning and development (e.g., Needham & Libertus, 2011).…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, active mittens training has been found to encourage grasping behaviors in infants at high familial risk for ASD (Libertus & Landa, 2014). Although improvements in infants' object exploration and focused attention on objects has been demonstrated in typically-developing infants (Libertus et al, 2016; Wiesen et al, 2016), long-term effects of sticky mittens training for at-risk infants remains unknown. Future research is needed to resolve these questions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that the ability to coordinate goal-directed action develops considerably in infancy (e.g., McCarty, Clifton, & Collard, 1999;von Hofsten, 1991). Several behavioral studies have demonstrated that infant motor behavior can index EF, the cognitive processes that support self-regulation, early in life (for review see: Diamond, 2006), and recent longitudinal (e.g., Libertus, Joh, & Needham, 2016) and correlational studies (Gottwald, Achermann, Marciszko, Lindskog, & Gredeback, 2016) suggest that infants' own actions are associated with broad improvements in attention and EF. Given these associations between infant action and EF (Gottwald et al, 2016;Libertus et al, 2016) and strong associations between EF and TOM (e.g., Austin, Groppe, & Elsner, 2014;Carlson, Mandell, & Williams, 2004), it could be that infants' control of their own actions is a precursor to EC, and that EC in turn predicts TOM.…”
Section: Research Highlightsmentioning
confidence: 99%
“…Several behavioral studies have demonstrated that infant motor behavior can index EF, the cognitive processes that support self‐regulation, early in life (for review see: Diamond, ), and recent longitudinal (e.g., Libertus, Joh, & Needham, ) and correlational studies (Gottwald, Achermann, Marciszko, Lindskog, & Gredeback, ) suggest that infants’ own actions are associated with broad improvements in attention and EF. Given these associations between infant action and EF (Gottwald et al, ; Libertus et al, ) and strong associations between EF and TOM (e.g., Austin, Groppe, & Elsner, ; Carlson, Mandell, & Williams, ), it could be that infants’ control of their own actions is a precursor to EC, and that EC in turn predicts TOM. In the current study, we explore both the possibilities that infant action execution is directly associated with TOM, and that neural processing during infant action execution could reflect developmental precursors for EC.…”
Section: Introductionmentioning
confidence: 99%